The landscape of SME financing and sustainability of SMEs in Bangladesh - Md Alamgir, , (2014)
Small and Medium Enterprises (SMEs)1 are the dominant form of business organization in all countries, generally representing more than 95% of the business population.OECD recognized that SMEs constitute an important dynamic element in all economies as they drive innovation and play a key role in driving sustainable economic growth, employment creation and poverty reduction, particularly in developing countries.It also contributes to the social, cultural and environmental capital of nations.SMEs are regarded by many governments and international developmental organizations as engines of innovation, economic growth, employment generation and poverty reduction. The role of Small and Medium Enterprises (SMEs) is indispensable for overall economic development of a developing country like Bangladesh. Since this sector is labor-intensive with short gestation period, it is capable of increasing national income as well as rapid employment generation of the marginalized people; achieving Millennium Development Goals (MDGs) especially eradication of extreme poverty and hunger, gender equality and women empowerment.SME sector has played a vital role in economic development of some developed countries of Asia especially Japan and Malaysia. Most of the Asian developing countries have also given due importance on SME.Terming SME as „employment generating machine‟ they stressed on SME development for higher economic growth, narrowing the gap of income inequality and poverty alleviation.The present government of Bangladesh has also put much emphasis on the development of SME sector considering it as „the driving force for industrialization‟.